Reliability and validity of the Brazilian version of the HSOPSC: a reassessment study - Reis, Cláudia Tartaglia; Laguardia, Josué; Barros, Cláudia Garcia de; Andreoli, Paola Bruno de Araujo; Martins, Mônica (Cadernos de saúde pública, 2019)
This study aimed to reassess the psychometric properties of the Hospital Survey on Patient Safety Culture (HSOPSC) adapted to Portuguese for use in the Brazilian context. An observational, cross-sectional study was performed in a large, private, non-profit, acute care hospital, reference in patient safety, in a major Brazilian metropolis. Participants were selected from a non-probability sample of all eligible personnel in the various hospital departments invited to participate in the study. Reliability of the HSOPSC was assessed by estimating Cronbach’s alpha for each dimension. confirmatory factor analysis (CFA), a matrix of correlations between the dimensions, and exploratory structural equation modelling (ESEM) were used in exploratory and confirmatory analyses of the structural validity of the construct. The overall response rate was 18.7% (n = 1,439). Four dimensions (“overall perceptions of patient safety”; “staffing”; “teamwork across units”; and “non-punitive response to error”) returned problems of internal consistency. CFA returned acceptable fit with the original 12-dimension model. Correlations between the dimensions of the original 12-dimension model indicated discriminant validity problems, while residual variance was greater than 0.70 in 13 items. The ESEM of the original 12-dimension model returned good fit, with the following indices: CFI = 0.985; TLI = 0.968, and RMSEA = 0.026 (90%CI: 0.024-0.029). Although better than those of the first evaluation, the results obtained in this validity and reliability reassessment of the Brazilian version of the HSOPSC require further research. Resumen: El estudio tuvo como objetivo revisar las propiedades psicométricas de la versión del Hospital Survey on Patient Safety Culture (HSOPSC) adaptado al portugués, para su uso en el contexto brasileño. Se realizó un estudio transversal observacional, en un hospital grande con cuidados intensivos, privado, sin ánimo de lucro, punto de referencia en seguridad del paciente, situado en una de las mayores metrópolis brasileñas. Los participantes se seleccionaron de un muestreo no probabilístico entre todo el personal elegible de los diversos departamentos hospitalarios invitados a participar en el estudio. La fiabilidad del HSOPSC se evaluó estimando el alfa de Cronbach para cada dimensión. Se utilizaron tanto el análisis factorial confirmatorio (AFC), como la matriz de correlaciones entre las dimensiones y los modelos de ecuaciones estructurales exploratorios (ESEM) en el análisis exploratorio y confirmatorio para la validez estructural del constructo. El porcentaje general de respuesta fue de un 18,7% (n = 1,439). Hubo cuatro dimensiones (“percepciones generales de seguridad del paciente”; “dotación de personal”; “trabajo en equipo en las unidades”; y “respuesta al error no-punitiva”), problemas recurrentes de consistencia interna. El AFC mostró un ajuste aceptable con el modelo original de 12-dimensiones. Las correlaciones entre las dimensiones del modelo original de 12-dimensiones indicaron problemas de validez discriminante, mientras que varianza residual era mayor a 0,70 en 13 ítems. Los ESEM del modelo original de 12-dimensiones tuvieron un buen ajuste con los siguientes índices: CFI = 0,985; TLI = 0,968 y RMSEA = 0,026 (90%CI: 0,024-0,029). A pesar de que eran mejores que los de la primera evaluación, los resultados obtenidos en esta revisión de la validez y fiabilidad de la versión del cuestionario, traducido y adaptado al contexto brasileño, es necesario que haya más investigaciones al respecto sobre este asunto. Resumo: O estudo teve como objetivo reavaliar as propriedades psicométricas da versão do Hospital Survey on Patient Safety Culture (HSOPSC) adaptada para o português, para uso no contexto brasileiro. Foi realizado um estudo observacional, transversal, em um hospital particular sem fins lucrativos, referência em segurança do paciente, localizado em uma metrópole brasileira. Os participantes foram selecionados a partir de uma amostra não-probabilística de todos os funcionários elegíveis de diversos departamentos hospitalares, convidados a participar no estudo. A confiabilidade do HSOPSC foi avaliada pela estimativa do alfa de Cronbach para cada dimensão. Foram usadas análise fatorial confirmatória (AFC), uma matriz de correlações entre as dimensões e modelagem de equações estruturais (MEE) na análise exploratória e confirmatória da validade estrutural do construto. Houve uma taxa global de resposta de 18,7% (n = 1.439). Quatro dimensões (“percepção geral de segurança do paciente”; “recursos humanos”; “trabalho de equipe entre unidades” e “resposta não-punitiva aos erros”) apresentaram problemas de consistência interna. A AFC mostrou um ajuste aceitável em relação ao modelo original de 12 dimensões. As correlações entre as dimensões do modelo original de 12 dimensões indicaram problemas de validade discriminante, enquanto a variância residual foi maior de 0,70 em 13 itens. A MEE do modelo original de 12 dimensões mostrou bom ajuste, com os seguintes índices: CFI = 0,985; TLI = 0,968 e RMSEA = 0,026 (IC90%: 0,024-0,029). Embora tenham superado a primeira avaliação, os resultados obtidos nesta reavaliação da validade e confiabilidade da versão do questionário traduzida e adaptada para o contexto brasileiro indicam a necessidade de mais estudos.